Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.ijom.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

New method for quantification of the relative severity and (a)symmetry of isolated metopic synostosis

Abstract: Trigonocephaly is the result of premature fusion of the metopic suture and its severity can vary widely. However, there is no gold standard for quantification of the severity. This study was performed to quantify severity using the Utrecht Cranial Shape Quantifier (UCSQ) and to assess forehead symmetry. Nineteen preoperative non-syndromic trigonocephaly patients (age 1 year) were included for the analysis of severity and symmetry. Severity according to the UCSQ was based on the following combined variables: fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Since little is known about the correlation between severity of trigonocephaly and its ICV, the present study correlated with the severity of the skull deformity according to UCSQ to ICV. In our previous study, we found high correlation between the UCSQ method and severity of trigonocephaly and is therefore proven to be eligible for quantification purposes in trigonocephaly patients (Kronig et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Since little is known about the correlation between severity of trigonocephaly and its ICV, the present study correlated with the severity of the skull deformity according to UCSQ to ICV. In our previous study, we found high correlation between the UCSQ method and severity of trigonocephaly and is therefore proven to be eligible for quantification purposes in trigonocephaly patients (Kronig et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study, we combined ΔY peak and width of frontal peak at F-0.05. A high correlation was found between severity of trigonocephaly and these combined variables (Kronig et al, 2021).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations